Video Based TM Training (VBTMT) - Nur Muizz, Mohamed Salleh (2008)
Basically the training process for most of Telekom Malaysia (TM) employee in Multimedia College (MMC) especially for company driven programmes is conducted through conventional way. In this situation, trainer will share all information regarding the program supported by pure printed material and slide presentation show. However the knowledge sharing processes are only available during the training session. A pure printed material doesn't always provide effective support for explanation because it only could provide information based on text and images. Since the company driven programs are compulsory for all TM employees, an alternative training material is required. Thus, video-based training has been identified as a suitable and potential alternative since it is could support more dynamic elements such as audio, text, visual and animation that allow trainee to do self training in any place at anytime. This paper discusses a Video-based TM Training (VBTMT), a content which has been developed for MMC trainee as a new training material that could provide more flexibility in term of trainer dependencies and training content quality. By using Powerpoint TM and Camtasia Studio software, the video-based training that focus on "Living the Brand for Supervisor Program" shows no significant compared result on experimental study for pre-test and post-test question regarding to the conventional and video-based training methodology. Results of user evaluation on the VBTMT indicate that it has good usability in terms of Usefulness, Ease of Use and Outcome/Future Use.